2019
DOI: 10.1186/s12985-019-1131-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding Chinese herb medicine ageratum-liquid on intestinal bacterial translocations induced by H9N2 AIV in mice

Abstract: Background As a low pathogenic influenza virus, avian influenza virus subtype H9N2 (H9N2 AIV) often induces high morbidity in association with secondary bacterial infections in chickens or mammals. To explore this phenomenon, the relationship between intestinal microflora changes and bacterial translocations was studied post H9N2 AIV challenge and post AIV infection plus Ageratum-liquid treatment. Methods Illumina sequencing, histological examination and Neongreen-tagge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Studies have shown that H9N2 AIV infection can promote the translocation of intestinal flora in mice [ 22 ], but the translocation of microflora in chicken intestine caused by H9N2 AIV infection is still unknown. Our study shows that H9N2 infection could promote translocation of the microflora from the intestinal metastasis to the mesentery, liver, and lungs in chickens at 5 dpi and 12 dpi.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that H9N2 AIV infection can promote the translocation of intestinal flora in mice [ 22 ], but the translocation of microflora in chicken intestine caused by H9N2 AIV infection is still unknown. Our study shows that H9N2 infection could promote translocation of the microflora from the intestinal metastasis to the mesentery, liver, and lungs in chickens at 5 dpi and 12 dpi.…”
Section: Resultsmentioning
confidence: 99%
“…To prevent the severe consequences of ZIKV infections and reduce ZIKV-induced neurological defects, an effective anti-ZIKV agent is required. Compounds isolated from natural plants have been widely evaluated in many antiviral studies [ 17 , 18 ]. Previous research on the natural Cephalotaxus alkaloids harringtonine, homoharringtonine, and cephalotaxine majorly showed antitumor effects, such as antileukemic activity [ 11 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Gegen Qinlian decoction can downregulate the expression of some signaling pathway factors and the activity of NF-κB, inhibiting the expression of inflammatory factors and the cytokine storm, affecting the differentiation of CD4 + T cells and thereby increasing the antiviral immunity of the host [ 107 , 108 ]. The Gegen Qinlian decoction activates the host’s homeostatic inflammatory response, limits immunopathological damage, and improves clinical symptoms [ 107 , 108 ]. Similarly, Lianhua-qingwen is a traditional Chinese medicine prescription for the treatment of respiratory diseases that can relieve clinical symptoms such as fever, cough, sore throat, and fatigue and has a broad-spectrum inhibitory effect on influenza virus [ 109 ].…”
Section: Development and Effects Of Influenza Antiviral Drugsmentioning
confidence: 99%